Projeto e construção de uma plataforma simuladora de entorse de tornozelo - França, Maaseias Barbosa [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
To attend the need of a problem from professionals in the physiotherapy area, arose the necessity of elaborating a mechanical project which could collaborate with studies developed in the area, on ankle sprains, such a problem is recurrent in the lives of people who play sports and has great relevance and need for research tha can diagnose and remedy such misfortune. The problem is to analyze parameters that can be collected during the simulation of ankle sprain and also the fatigue of the fibular muscles, because according to studies, a great part of the sprains are caused after a lot of physical effort. With this, a solution was elaborated in which it consists of constructing a simulator platform of sprain in inversion. The platform was designed to meet two parameters of extreme relevance: inducing fatigue of the fibular muscles and later simulating the ankle sprain for a maximum angle of 30 ° to the horizontal in which it rotates around two Cartesian axes, ie, x and y, thus providing the combined movement of the ankle. For fatigue induction, two transducers were used that convert voltage into an electrical signal that is sent to a device known as an electromyograph. The induction occurs through the effort that individual exerts through a strap that surrounds his foot, which has one end, connected to the transducer and the other, by hugging the foot of the volunteer, is fixed to the upper floor in which the individual is standing. Then for simulation of ankle sprain the same top floor which is fixed to a top structure which in turn connects to another intermediate surface realizes the conjugate movement when it is mechanically driven through the researcher releasing suddenly causing the individual to twist the feet. During the fall is collected is measured the speed through a device called inductive sensor that measures the speed of ... (Complete abstract click electronic access below)

Para atender a necessidade de um problema na área de fisioterapia, surgiu a ideia de elaborar um projeto mecânico que pudesse corroborar com estudos desenvolvidos na área, sobre entorse de tornozelos, tal problema é recorrente na vida de pessoas que praticam esportes. O projeto consiste em um equipamento mecânico que simule a entorse de tornozelo e fadiga dos músculos fibulares, que fornece parâmetros a serem analisados durante a simulação, pois segundo estudos, grande parte das entorses são causadas depois de muito esforço físico. Com isso, elaborou-se uma solução no qual consiste em construir uma plataforma simuladora de entorse em inversão. A plataforma foi projetada de maneira a atender a dois parâmetros de extrema relevância que são: indução a fadiga dos músculos fibulares e posteriormente simula a entorse do tornozelo para um ângulo máximo de 30° em relação a horizontal no qual o mesmo gira em torno de dois eixos cartesianos, ou seja, x e y propiciando assim o movimento combinado do tornozelo. Para indução a fadiga, foram utilizados dois transdutores que converte tensão em sinal elétrico que é enviado a amplificador de sinal que efetua a leitura. A indução ocorre através do esforço que indivíduo exerce por meio de uma cinta que envolve o seu pé, que tem uma das extremidades, conectada ao transdutor, e a outra abraçando o pé do voluntário, é fixada ao piso superior no qual o indivíduo se encontra em pé. Em seguida para simulação de entorse de tornozelo o mesmo piso superior que está fixado a uma estrutura superior que por sua vez conecta-se a outra superfície intermediaria que realiza o movimento conjugado quando é acionado mecanicamente através do pesquisador que libera repentinamente fazendo com que o indivíduo torça o pé. Durante a queda é colhido o tempo, através de um ... (Resumo completo, clicar acesso eletrônico abaixo)
Design and construction of an ankle sprain simulator platform
Keywords: Entorse; Musculos - Ferimentos e lesões; Fisioterapia; Sprain